Le traitement du terrorisme dans les Historiciclos de Forges : du choix de la case vide - Olivier Ruaud (Cahiers de Civilisation Espagnole Contemporaine)
In 1977, drawer Antonio Fraguas de Pablo-Forges- published comics in Los Historiciclos, a story of Spain under Franco with different narrative technics. This paper is focused on his vision of terrorism and specially eta’s action. Because of the peculiar style of the comic, Forges never drawn violence and preferred humour, another information or just text, copying information technics of Franco’s dictatorship, excepting humour. This choice is not easy but sometimes, this empty vignette tells more than words and draws. This is what Forges offered to the reader.